(untitled) (GYMNASIUM, 2009)
The development of speed skating has met lately a spectacular evolution also in the countries that have a relatively new tradition in this sport, countries that, of many times, have borrowed methods and means from countries with an older tradition in speed skating, adapting to the bio-psycho-somatic characteristics specific to the zones but also, and not in the last place, to the existent base in these countries. This paper points out some of the main training methods used by great champions, methods developed by foreign and Romanian scientific investigators.